Pancreatic Neuroendocrine Tumors: Role of Novel Agents - Strimpakos, Alexios S; Syrigos, Kostas N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
Neuroendocrine tumors of pancreas (PNET) are very rare, consisting of heterogeneous histological subtypes with a variable natural history and different clinical manifestations. Although the vast majority of these neoplasms are sporadic, it is possible to be part of a genetic syndrome such as multiple endocrine neoplasia 1 (MEN-1) or tuberous sclerosis (TSC). When systemic treatment is required the options are limited and management strategy is generally based on experts’ consensus or clinical experience. The prognosis is usually better than in pancreatic adenocarcinoma, though poorly differentiated PNET behave aggressively and survival is shortened. Since last year, there has been a significant advance in the management of PNET, after reported data confirmed the efficacy of everolimus, an mTOR inhibitor, in patients with advanced disease. At the 2011 American Society of Clinical Oncology (ASCO) Gastrointestinal Symposium, updated results of the phase III trial (RADIANT-3) regarding the efficacy of everolimus in PNET (Abstract #158) were reported, along with the results of a subgroup analysis of the Japanese patients enrolled in this study (Abstract #289). Another agent with promising activity in PNET which will be discussed in this review is sunitinib, a biological agent with multikinase inhibitor properties (Abstract #244). Image: Sotiria General Hospital. Athens, Greece.